Trade Facilitation and Gender Dimensions in South Africa : Survey Findings and Recommendations - World Bank (World Bank, Washington, DC, 2022)
Access to international markets plays a critical role in an economy’s growth and development. Trade facilitation, the simplification, modernization, and harmonization of export and import processes has therefore emerged as an important issue for countries, as is reflected in the World Trade Organization Trade Facilitation Agreement (WTO TFA), which came into effect on February 22, 2017. Increasingly, it is recognized that women traders face particular challenges when undertaking cross-border trade, such as lack of information and knowledge of cross-border regulations and procedures, lack of physical security at border crossings, exposure to harassment and gender-based violence at borders, and corruption. This report presents the results of a survey on trade facilitation challenges faced by traders and customs agents in South Africa. The survey also explored trade facilitation challenges related to Coronavirus (COVID-19).